2017
DOI: 10.3390/app7010097
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Soy Contents in Ground Beef Using Near-Infrared Spectroscopy

Abstract: Models for determining contents of soy products in ground beef were developed using near-infrared (NIR) spectroscopy. Samples were prepared by mixing four kinds of soybean protein products (Arconet, toasted soy grits, Profam and textured vegetable protein (TVP)) with ground beef (content from 0%-100%). NIR spectra of meat mixtures were measured with dispersive (400-2500 nm) and Fourier transform NIR (FT-NIR) spectrometers (1000-2500 nm). Partial least squares (PLS) regression with full leave-one-out cross-vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…In this method, R 2 = 0.81 for the starch value of DDGS, R 2 = 0.88 for protein and R 2 = 0.87 for moisture (Paulsen et al 2010). In a study to determine protein, starch and fat content of maize by using of NIR device (Jiang et al 2017); protein, starch, and fat contents were found to be the same as the results determined by wet chemical method. The researchers concluded that the NIR method can be used to quickly detect protein, starch and fat content.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this method, R 2 = 0.81 for the starch value of DDGS, R 2 = 0.88 for protein and R 2 = 0.87 for moisture (Paulsen et al 2010). In a study to determine protein, starch and fat content of maize by using of NIR device (Jiang et al 2017); protein, starch, and fat contents were found to be the same as the results determined by wet chemical method. The researchers concluded that the NIR method can be used to quickly detect protein, starch and fat content.…”
Section: Introductionmentioning
confidence: 54%
“…Although not the same type of studies, there are logically similar quantitative studies to detect adulteration tricks in feedstuffs or food for human consumption. From 0% to 30% of meat (0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%,20%, 25% and 30%) Rcv2 (cross validation) value was determined in the range of 0.99-0.98 in adulteration study by adding 4 different soy flour (Jiang et al 2017). As a result, it was demonstrated by using the FT-NIR method that the soy products added to meat products such as sausage, salami and sausage can be quantitatively determined.…”
Section: Discussionmentioning
confidence: 99%
“…PC-1 showed that 97% of the total variance observed consisted of bands at 1450, 1880 and 2030 nm (Figure 5). Previous studies have shown that bands at approximately 1880 nm correspond to fatty acids 28 and 2023 nm correspond to N–H bond in amides. 29 Among the bands found in PC-2 that accounted for 2% of the total variance observed, only the peaks at 1450 and 1930 nm were previously identified as water.…”
Section: Resultsmentioning
confidence: 99%
“…Pada spektrum ini terlihat beberapa komponenkomponen penting yang terdapat didalamnya. Komponen air dimana pada prinsipnya daging yang diukur mengandung air yang terlihat pada daerah bilangan gelombang 7067 cm −1 dimana dijelaskan lebih khusus oleh [7] bahwa pada daerah panjang gelombang 1415 nm atau setara dengan energi pada bilangan gelombang 7067 cm −1 merupakan pengelompokan karakteristik untuk air, sedangkan untuk protein ditunjukan pada daerah bilangan gelombang 4578 cm −1 , hal ini juga sudah dijelaskan terlebih dahulu oleh [15] bahwa serapan protein terdapat pada panjang gelombang 2061 dan 2184 nm atau 4852 dan 4578 cm −1 . Selain itu komponen lemak juga terlihat muncul pada daerah bilangan gelombang 8280 cm −1 hal ini juga dapat disesuaikan dari gambar spektrum lemak yang disandingkan pada Gambar 3.…”
Section: Gambar 4: Spektrum Hasil Normalisasi Dan Smoothingunclassified